2021
DOI: 10.1177/0731684421997924
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of glulam timber beam strengthened with carbon fiber reinforced polymer strip for flexural loading

Abstract: In the last 20 years, the use of wooden structures and their dimensions have gradually increased. The wood application has increased in different structures such as multistory buildings, sports, industrial facilities, road and railway bridges, power transmission lines, and towers. The widespread use and size of wood structures have increased the research on developing special types of wood products supported by composite materials. Laminated wood elements are the leading composite wood materials. Laminated woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In this way, a load increase of 92% and a displacement increase of 14% were obtained compared to the reference sample. In many studies, the reinforcement of wooden beams with FRP layers (more than three layers) both reduces e ciency and increases costs [40,41,42]. It was observed that CFRP-reinforced wooden beams increase the load bearing capacity by more than 50% and exhibit a ductile behavior.…”
Section: Load-de Ection Curve Of Timber Beams Reinforced With Cfrp An...mentioning
confidence: 99%
“…In this way, a load increase of 92% and a displacement increase of 14% were obtained compared to the reference sample. In many studies, the reinforcement of wooden beams with FRP layers (more than three layers) both reduces e ciency and increases costs [40,41,42]. It was observed that CFRP-reinforced wooden beams increase the load bearing capacity by more than 50% and exhibit a ductile behavior.…”
Section: Load-de Ection Curve Of Timber Beams Reinforced With Cfrp An...mentioning
confidence: 99%
“…In this way, a load increase of 92% and a displacement increase of 14% were obtained compared to the reference sample. In many studies, the reinforcement of wooden beams with FRP layers (more than threelayers) both reduces e ciency and increases costs [40,41,42]. It was observed that CFRP-reinforced wooden beams increase the load bearing capacity by more than 50% and exhibit a ductile behavior.…”
Section: 3load-de Ection Curve Of Timber Beams Reinforced With Cfrp A...mentioning
confidence: 99%
“…Thus, a load increase of 92% and displacement increase of 14% were obtained compared with the reference sample. In many studies, reinforcing wooden beams with FRP layers (more than three layers) reduced efficiency and increased costs (İşleyen et al, 2021;Ling et al, 2020;Rescalvo et al, 2018a). It was observed that the CFRP-reinforced wooden beams increased the load-bearing capacity by more than 50% and exhibited ductile behavior.…”
Section: Load-deflection Curve Of Timber Beams Reinforced With Carbon...mentioning
confidence: 99%